iOS 16 programming for beginners : kickstart your iOS app development journey with a hands-on guide to Swift 5.7 and Xcode 14 - Sahar, Ahmad; Clayton, Craig (Expert insight., 2022)
With almost 2 million apps on the App Store, iOS mobile apps continue to be incredibly popular. Anyone can reach millions of customers around the world by publishing their apps on the App Store, which means that competent iOS developers are in high demand. iOS 16 Programming for Beginners, Seventh Edition, is a comprehensive introduction for those who are new to iOS, covering the entire process of learning the Swift language, writing your own app, and publishing it on the App Store. This book follows a hands-on approach. With step-by-step tutorials to real-life examples and easy-to-understand explanations of complicated topics, each chapter will help you learn and practice the Swift language to build your apps and introduce exciting new technologies to incorporate into your apps. You'll learn how to publish iOS apps and work with new iOS 16 features such as Mac Catalyst, SwiftUI, Lock Screen widgets, WeatherKit, and much more. By the end of this iOS development book, you'll have the knowledge and skills to write and publish interesting apps, and more importantly, to use the online resources available to enhance your app development journey.